DAMPAK ASAS IMUNITAS TERHADAP PENYELESAIAN PERSELISIHAN HUBUNGAN KERJA ANTARA PEGAWAI SETEMPAT (LOCAL STAFF) DENGAN PERWAKILAN NEGARA ASING - Susanti, Ida (Faculty of Law, Parahyangan Catholic University, 2022)
The employment agreement between local staff and Representatives of Foreign Countries (RFC) is very problematic, because many people believe that a RFC has the immunity to be sued before the court where the RFC is located. Applicability of this immunity to employment agreement’s disputes between the local staff and the RFC is debatable. This paper will examine restrictions on the application of the principle of immunity in employment agreements, and how these exemptions impact legal protection for local staff. Therefore, using the normative/doctrinal approach, this paper will discuss the meaning of the immunity principle and its application in the employment relationship between RFC and local staff; the jurisdiction of the local court to resolve disputes between local staff and the RFC; and the impact of the limitation of the principle of immunity to the legal protection that will be provided to local staff with RFCs. Those will be seen both in regulations, court decision and opinio-doctorum. Finally, this paper will recommend parameters for determining the criteria to limit the application of the immunity principle in the employment agreement.